The economic value of electricity in the kitchen - Hamilton, Mary L.; Forsyth, M. Edith (My University, 1906)
Introduction: The object of the Thesis was to test for the comparative cost of coal, gasoline and electricity in the home, and for practical use in the kitchen and to determine the economical use of electricity. Three tests were suggested; ironing, baking bread, and preparing a meal on the three different stoves, coal, gasoline and on electricity. In summing up the tests, first in the ironing test, it was found that less work was done with the coal than by any other method. The most work being done by electricity, the heat being constant no time was wasted, thus, in the end being the cheapest. In baking, the gasoline was the quickest method, the electrical oven being hard to regulate and to keep at an even temperature. The degree of heat was much easier controlled by gasoline and for baking purposes it proved to be the best. The electrical tests were the most expensive made but we have to take into account the high rate charged in Manhattan, fifteen cents per 'Kilowatt hour, while in other cities it is much less, the lowest city rate being about five cents per Kilowatt hour. Thus the cost would be one third as much as that at Manhattan, but would still be expensive. In order to be as cheap as gasoline and coal the rate would have to be one and a half cent per Kilowatt hour. In winter time provided the house was heated with steam or hot air the gasoline could be used as cheap as coal, but where kitchen must be heated the coal would prove the cheapest. If in the future, different forms of apparatus would be devised as undoubtedly will be, it will simplify everything and make cooking with electricity within reach of all. It would be difficult to say whether the increasing demands for fancy dishes has brought about improved apparatus for cooking or that the new devices for cooking has brought about fancy dishes, but the new and various forms and methods by which heat developed by electricity can be used may be of great aid to all kinds of cooking in the future.
Citation: Hamilton, Mary L. and Forsyth, M. Edith. The economic value of electricity in the kitchen. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Home Economics; Utility Expenses; Cooking; Electricity; Theses